A large-scale optimization model for tactical wood procurement planning - Lehtonen, Eero (My University, 2016)
Large-scale wood sourcing requires complex planning processes that are often supported by optimization models. This thesis focuses on tactical wood sourcing at a large Finnish forest industry company. The company is building a new planning system in order to improve upon the current process that involves a less detailed model and requires large amounts of manual work to produce plans that can be implemented. The target of the new planning system is to improve decision making by providing a more accurate planning system and reducing manual efforts. In this thesis, the wood procurement problem is formulated as a large linear programming model. The model is a multi-commodity flow problem with varying harvesting yields, multiple transportation modes, storage management, by-product generation and end-product substitution. This formulation is then solved with a commercial optimization solver resulting in a running time of some tens of minutes. Different results under varying input scenarios are presented and elaborated to demonstrate the model's ability to capture the essentials of the complex problem. The model's suitability for both continuous planning and what-if scenario work is also discussed. Solving ill-structured real life problems using mathematical modeling techniques is difficult for two reasons in particular: i) the actual modeling work can be technically and process-wise a major challenge in a real business environment, and ii) the computational complexity borne of the business environment's features may involve severe challenges in solving such models and implementing useful decision support systems. This thesis presents a case where both difficulties were present and somewhat successfully overcome.

Laajamittainen puunhankinta edellyttää monivaiheista suunnitteluprosessia, jota yleensä tuetaan optimointimalleilla. Tämä työ keskittyy erään suuren suomalaisen metsäteollisuuskonsernin puunhankintaan. Yhtiö kehittää parhaillaan uutta suunnittelujärjestelmää, jonka on tarkoitus parantaa nykyistä suunnitteluprosessia, jossa käytetään karkeampaa optimointimallia, ja joka vaatii suuren määrän käsityötä käytännöllisen hankintasuunnitelman tuottamiseksi. Hankkeen tarkoituksena on parantaa päätöksentekoa tuottamalla entistä tarkempi suunnittelujärjestelmä, joka samalla vähentää käsityön tarvetta. Tässä työssä puunhankintaongelma on esitetty suurena lineaarisena optimointitehtävänä. Kehitetty malli on monen hyödykkeen virtausongelma, joka sisältää vaihtelevia hakkuiden lankeamia, useampia kuljetusmuotoja, varastonhallintaa, sivutuotteiden syntymistä ja kysynnän substituutteja. Tämä tehtävän ratkaisu kaupallisella ratkaisijalla kestää joitain kymmeniä minuutteja. Työssä käsitellään eri skenaarioiden tuottamia ratkaisuja ja esitellään mallin kykyä huomioida monimutkaisen ongelman avaintekijöitä. Työssä käsitellään myös mallin sopivuutta jatkuvaan suunnitteluun ja skenaariopohjaiseen analyysiin. Erityisesti kaksi tekijää vaikeuttavat matemaattisen mallintamisen soveltamista käytännön ongelmiin: i) mallinnustyö voi olla teknisesti ja prosessin kannalta haasteellista liiketoiminnan käytännöissä, ja ii) toimintaympäristön ominaisuuksista aiheutuva laskennallinen monimutkaisuus voi tuottaa haasteita mallin ratkaisemisessa ja sen tulosten hyödyntämisessä. Tämä työ käsittelee tapausta, joissa kumpikin haaste ilmeni, ja joista kumpikin saatiin ainakin osittain ratkaistua.
Laaja optimointimalli taktiseen puunhankinnan suunnitteluun
Keywords: wood sourcing; supply chain management; decision support systems; tactical planning; linear programming